2022
DOI: 10.1093/cid/ciac290
|View full text |Cite|
|
Sign up to set email alerts
|

Two-Dose Severe Acute Respiratory Syndrome Coronavirus 2 Vaccine Effectiveness With Mixed Schedules and Extended Dosing Intervals: Test-Negative Design Studies From British Columbia and Quebec, Canada

Abstract: Background The Canadian COVID-19 immunization strategy deferred second doses and allowed mixed schedules. We compared two-dose vaccine effectiveness (VE) by vaccine type (mRNA and/or ChAdOx1), interval between doses, and time since second dose in two of Canada’s larger provinces. Methods Two-dose VE against SARS-CoV-2 infection or hospitalization among adults ≥18-years-old, including due to Alpha, Gamma and Delta variants of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 24 publications
12
79
1
3
Order By: Relevance
“…Nonetheless, a growing number of studies suggest that an extended dosing interval amplifies both the humoral immune response 30 and perhaps the cellular response, 31 and is an effective global strategy given the discrepancies between regions with high and low vaccination coverage. 32 But even recent studies have so far only investigated the second dose and have not evaluated responses to the omicron variant. 30 33 Our present analysis showed that receiving the third dose later (that is, after August 2021) was associated with slight protection against infection, but was not significantly associated with the odds of hospital admission or death related to covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a growing number of studies suggest that an extended dosing interval amplifies both the humoral immune response 30 and perhaps the cellular response, 31 and is an effective global strategy given the discrepancies between regions with high and low vaccination coverage. 32 But even recent studies have so far only investigated the second dose and have not evaluated responses to the omicron variant. 30 33 Our present analysis showed that receiving the third dose later (that is, after August 2021) was associated with slight protection against infection, but was not significantly associated with the odds of hospital admission or death related to covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…Second doses were deferred up to 16 weeks with third doses also beginning with the oldest in December 2021 ( Supplementary Figure 1 ). 10,11…”
Section: Methodsmentioning
confidence: 99%
“…The negative test case–control study from Canada showed that AZD1222 against documented infection for Gamma was surprisingly effective ( 50 ). However, the study from Brazil revealed that the VE of double-dose AstraZeneca-Vaxzevria vaccine was 88.1% (95% CI: 82.8–91.7) ( 56 ) ( Table 3 ).…”
Section: Covid-19 Vaccine Effectiveness Against Variantsmentioning
confidence: 99%
“…Peer-reviewed studies from Spain also demonstrated that AZD1222 was 55% (95% CI: 39–67) effective against documented infection for the Delta variant ( 41 ). The results of the negative test case–control study from Canada revealed that the VE against hospitalization due to Delta was >90% ≥14 days following the 2nd dose ( 50 ). Furthermore, the VE of AZD1222 against death caused by the Delta variant was 91% (95% CI: 86–94) in the evaluation of the VE of AZD1222 preventing death among 380,532 residents in British Columbia including 27,439 cases ≥14 days following the second dose ( 62 ) ( Table 3 ).…”
Section: Covid-19 Vaccine Effectiveness Against Variantsmentioning
confidence: 99%